Efficacy and safety of a selective URAT1 inhibitor SHR4640 in Chinese subjects with hyperuricaemia: a randomized controlled phase II study. (8th March 2021) - Lin, Yanwei; Chen, Xiaoxiang; Ding, Huihua; Ye, Ping; Gu, Jieruo; Wang, Xiaoxia; Jiang, Zhenyu; Li, Detian; Wang, Zhongming; Long, Wubin; Li, Zhijun; Jiang, Gengru; et al.
Abstract: Objective: To evaluate the efficacy and safety of SHR4640, a highly selective urate transporter 1 inhibitor, in Chinese subjects with hyperuricaemia. Methods: This was a randomized double-blind dose-ranging phase II study. Subjects whose serum uric acid (sUA) levels were ≥480 µmol/l with gout, ≥480 µmol/l without gout but with comorbidities, or ≥540 µmol/l were enrolled. Subjects were randomly assigned (1:1:1:1:1) to receive once daily 2.5 mg, 5 mg, 10 mg of SHR4640, 50 mg of benzbromarone or placebo, respectively. The primary end point was the proportion of subjects who achieved target sUA level of ≤360 µmol/l at week 5. Results: 99.5% of subjects (n = 197) were male and 95.9% of subjects had gout history. The proportions of subjects who achieved target sUA at week 5 were 32.5%, 72.5% and 61.5% in the 5 mg, 10 mg SHR4640 and benzbromarone groups, respectively, significantly higher than the placebo group (0%; P < 0.05 for 5 mg and 10 mg SHR4640 group). The sUA was reduced by 32.7%, 46.8% and 41.8% at week 5 with 5 mg, 10 mg SHR4640 and benzbromarone, respectively, vs placebo (5.9%; P < 0.001 for each comparison). The incidences of gout flares requiring intervention were similar among all groups. Occurrences of treatment-emergent adverse events (TEAEs) were comparable across all groups, and serious TEAEs were not reported. Conclusions: The present study indicated a superior sUA-lowering effect and well tolerated safety profile after 5-week treatment with once-daily 5 mg/10 mg of SHR4640 as compared with placebo in Chinese subjects with hyperuricaemia. Trial registration: ClinicalTrials.gov number, NCT03185793